Development of sub-product from the waste from bacaba processing (oenocarpus bacaba Mart) as a source of value aggregation and income generation (Research, Society and Development, 2021)
The integral use of fruits in the elaboration of new products is a clean and viable technological alternative. This type of utilization is necessary to allow the fruit considered seasonal to be available to the consumer throughout the year, adding value and generating income for the communities that produce them. The aim of this study was to use the residue of bacaba processing in the elaboration of a jelly, contemplating the whole cycle of information necessary for this product to be in the market, focusing on income generation for the producers of this fruit. The composition of the raw material used for processing was initially determined. After that, the jelly formulations were developed and the best formulation was stored for the determination of its shelf life and analysis of its production viability. It was possible to obtain a jelly formulation that will promote the valuation of a by-product that would be discarded generating a market alternative for small and medium producers.